Risk Management Strategies in Blockchain Adoption within Financial Institutions Analyzing Challenges and Opportunities - Dewi, Susanti; Firasati, Aoliyah; Sitoayu, Laras; Bennet, Daniel (APTISI Transactions on Management (ATM), 2025)
The integration of blockchain technology in financial institutions has introduced both groundbreaking opportunities and significant risks, necessitating a comprehensive approach to risk management. Blockchain’s potential to enhance transparency, security, and efficiency in financial processes makes it an attractive technology for financial institutions. However, issues like regulatory uncertainty, data privacy, and technological readiness present unique challenges. This study aims to identify, evaluate, and provide insights into the primary risks associated with blockchain implementation in financial institutions, focusing on both challenges and opportunities to aid in effective risk management. Using the Structural Equation Modeling (SEM) technique with Partial Least Squares (PLS), also known as SmartPLS, this study examines data collected from financial industry stakeholders, including risk managers and IT experts. Variables assessed include data security, regulatory compliance, and technological infrastructure, allowing for a nuanced understanding of the risk dynamics within blockchain adoption. The analysis reveals that data security risks and regulatory concerns significantly impact blockchain implementation success, while technological readiness serves as a moderating factor, influencing the ease of adoption and operational success. Findings underscore the need for a balanced approach to blockchain integration in financial services, where risk management strategies address both regulatory and technological challenges. By identifying these core risks and their implications, this study contributes to the body of knowledge on blockchain risk management and offers practical recommendations for financial institutions aiming to adopt blockchain effectively while minimizing associated risks.